Control of expression of the ICE R391 encoded UV-inducible cell-sensitising function - Armshaw, Patricia (BioMed Central, 2013)
BACKGROUND: Many SXT/R391-like enterobacterial Integrative Conjugative Elements (ICEs) have been found to express an atypical, recA-dependent, UV-inducible, cell-sensitising phenotype observed as a reduction in post-irradiation cell survival rates in host cells. Characterisation of a complete deletion library of the prototype ICE R391 identified the involvement of three core ICE genes, orfs90/91 encoding a putative transcriptional enhancer complex, and orf43, encoding a putative type IV secretion system, outer membrane-associated, conjugative transfer protein. RESULTS: In this study, expression analysis of orf43 indicated that it was up-regulated as a result of UV irradiation in an orfs90/91-dependent manner. Induced expression was found to be controlled from a site preceding the gene which required functional orfs90/91. Expression of orfs90/91 was in turn found to be regulated by orf96, a λ cI-like regulator. Targeted construction of ICE R391 deletions, RT-PCR and qRT-PCR analysis confirmed a regulatory link between orfs90/91 and orf43 while site-directed mutagenesis of orf43 suggested an association with the cell membrane was a prerequisite for the cytotoxic effect. CONCLUSIONS: Because of the recA-dependence of the effect, we hypothesise that UV induction of RecA results in cleavage of the cI-like ICE-encoded repressor protein, the product of orf96. This in turn allows expression of the transcriptional enhancer complex encoded by orfs90/91, which we conclude stimulates transcription of orf43, whose product is directly responsible for the effect.